(untitled) (Research, Society and Development, 2021)
Introduction: It is observed over the last few decades that there has been a growth in the world of childhood obesity, and due to its evident growth it has been characterized as a new worldwide epidemic Objective: to analyze the aspects surrounding childhood obesity and its prevalence in current Society. Methodology: This study is an integrative literature review research. Results and Discussion: Obesity, already in childhood, is related to several complications, as well as to a higher mortality rate. And, the longer the individual remains obese, the greater the chance of complications occurring, as well as earlier. Conclusion: Actions at the collective level must involve public policies that promote the health, well-being and quality of life of the populations.